1997
DOI: 10.1088/0022-3727/30/17/016
|View full text |Cite
|
Sign up to set email alerts
|

A Müser - Curzon - Ahlborn engine model for photothermal conversion

Abstract: We study a photothermal engine resulting from a combination of a Müser engine with an endoreversible Curzon - Ahlborn cycle. This model was proposed by De Vos as an approach to a certain class of photothermal conversion devices. We analyse that engine with and without solar concentrators. We find that typical performance quantities such as the power output, entropy production, engine efficiency and solar conversion efficiency are functions both of the collector's temperature and of the concentration factor. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Whilst a solar cell is assumed as an endoreversible system [4], the energy conversion efficiency is limited to 85.7% this figure is obtained where the sun is assumed fully surrounding the cell (maximum concentration). If we bear in mind that in a real situation the solar cell does not operate always in maximum concentration and the solid angle under which the cell sees the sun is in fact only a minute fraction of a hemisphere, the maximum efficiency is not larger than 12.79%, which is actually lower than most recently fabricated solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst a solar cell is assumed as an endoreversible system [4], the energy conversion efficiency is limited to 85.7% this figure is obtained where the sun is assumed fully surrounding the cell (maximum concentration). If we bear in mind that in a real situation the solar cell does not operate always in maximum concentration and the solid angle under which the cell sees the sun is in fact only a minute fraction of a hemisphere, the maximum efficiency is not larger than 12.79%, which is actually lower than most recently fabricated solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…-2 Fig. 6. System efficiency at optimal receiver temperature versus receiver overall heat transfer coefficient, I R = 100 kWm -2 As high values of HTC are approached, the system behaviour tends towards that of a Mueser engine (Fig.…”
Section: Fig 4 System Efficiency At Optimal Receiver Temperature Vementioning
confidence: 99%
“…In the case of a direct steam solar thermal power plant, this resistance will manifest itself in the heat transfer coefficient associated with the boiling of water within the solar receiver pipes. Navarrete-Gonzalez et al [6,7] broached this matter and found that there appeared to be an optimal level of geometric concentration at which a solar thermal system's efficiency was maximised. What was not clear, however, was how this optimum affected real solar thermal plant designs.…”
Section: Fig 1 Mueser Enginementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper [1], we have analysed a photothermal conversion engine model based on a combination of the Müser and Curzon-Ahlborn engines as depicted in figure 1. This model was proposed by De Vos [2] as a suitable array for reproducing some solar conversion devices such as the Eurelios farm in Adrano, Italy.…”
mentioning
confidence: 99%